Empirical Study on the Relationship Between Vacation Schedule and Seafarers’ Fatigue in Chinese Seafarer Population - An, Ji; Gao, Wenting; Liu, Runze; Liu, Ziqi (Frontiers in Psychology, 2022)
Background Fatigue is an important factor for the safety of ships. In order to alleviate fatigue of the seafarers, the STCW Convention (International Convention on Standards of Training, Certification, and Watchkeeping for Seafarers) has made many regulations on the working time of seafarers. At present, if a crew member takes only one day off at home before returning to work on the ship, the working time on the ship must be re-calculated again. If the time spent at home is not sufficient to allow the crew to recover, the regulations of only stipulating the working time, not stipulating the home vacation time, cannot guarantee the crew’s fatigue been well controlled. The aim of present study is to explore the relationship between vacation schedule and fatigue of the seafarers. Methods In present study, a simplified stress scale developed by the Ministry of Labor of Japan has been used as a measurement tool. The method of stratified sampling was adopted. Data collection mainly came from domestic ocean-going seafarers (n = 165). Analysis was conducted using the Cross (chi-square) analysis and hierarchical multiple regression analysis methods. Results We found that there was no difference between crew members of different positions in terms of average vacation time and on-board service time (p > 0.05). The length of last vacation time and this service time for seafarers of different positions showed obvious differences (p < 0.01). The rank has a significant effect on the length of the last vacation (χ2 = 101.560, p = 0.000 < 0.01) and the length of this service time (χ2 = 75.624, p = 0.000 < 0.01). Also, the results showed that there was a significant negative correlation between the duration of vacation and overall fatigue (t = –7.160, p = 0.000 < 0.01), while there was a significant positive correlation between the length of service time on board and overall fatigue (t = 3.474, p = 0.001 < 0.01). Conclusion The results indicated that a reasonable vacation schedule was crucial for the relief of the seafarers’ fatigue, and also played a positive role in the state of working on the ship again.